(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
In the expression of Japanese giving and receiving, "te morau" is characterized by wide application, complex and varied usage, and changes in grammatical functions according to different contexts, etc. and often becomes one of the difficulties for Chinese, Japanese learners. Taking "te moraute morau" sentence as the research object, this paper analyzes the example sentences extracted from the corpus sorts out its usage from the aspect of causative and reactive voice, the benefactive and non-benefactive construction, and analyzes its grammatical function. Through the investigation and analysis of this paper, it is found that the usage of "te moraute morau" sentence can be divided into two categories, namely, benefactive expression and non-benefactive expression, both of which have causative and passive grammatical functions. In the extracted example sentences, the causative usage of the receiving subject as the heartless object is not observed, the reason is that the nonliving thing cannot actively promote the occurrence of the action. Non-benefactive usage of the receiving subject and the subject of action is limited to a character and don’t include nonliving things. This paper has a certain enlightening effect to Japanese learners, and can be of value to Japanese teaching. Япон хэлний өгөх, авах утгат туслах үйл үг -te morau хэллэгийн утга, хэрэглээний онцлог Хураангуй: Япон хэлэнд “-ж өгөх”, “-ж авах” хэмээх утга илэрхийлдэг -te morau туслах үйл үг нь яриа ба бичгийн хэлэнд утгын өргөн хүрээнд хэрэглэгддэг, олон хэрэглээтэй, хэлний орчны харилцан адилгүй нөхцөл байдлаас шалтгаалан хэл зүйн утга ч өөрчлөгддөг нь суралцагчдын хувьд сурах бэрхшээлүүдийн нэг болдог юм. Энэхүү өгүүлэлдээ хэлний материалын сангаас -te morau туслах үйл үг бүхий өгүүлбэрийг түүвэрлэн авч утга, хэрэглээнд дүн шинжилгээ хийхэд тустай (benefactive) болон тусгүй (non-benefactive) утгын илэрхийлэл гэсэн хоёр ангилалд хуваагдаж, мөн тус тус идэвхт байдал, идэвхгүй байдлын хэмээх утга агуулдаг болохыг олж мэдлээ. Түлхүүр үг: утга, тустай, тусгүй утга, идэвхт, идэвхгүй байдал